Molecular Characterization and Gene Expression Of TLR4 Gene Associated with Mastitis in Goats - S S Soquila; Arren Christian de Guia; N P Medina; C N Mingala (Indonesian Center for Animal Research and Development (ICARD), 2022)
In this study characterization of Toll-like receptor 4 (TLR4) gene of goats; detection of polymorphisms in the nucleotides, and determination of the association of identified genotypes with the occurrence of subclinical mastitis was done using chi-square and odds ratio. Analyzing gene expression using two-sided Student's T-test was also done. Results of Study 1 revealed high similarity (99%) of TLR4 nucleotide sequence of all breeds of goats with that of C. hircus (NM_001285574.1) and sheep (Ovis aries) sequences and slightly lower similarity with cattle (Bos taurus, and Bos indicus) (96%), and water buffalo (Bubalus bubalis) (95%). In Study 2, restriction fragment length polymorphism (RFLP) analysis revealed three genotypes with nine restriction patterns using AluI enzyme. Genotype AA has odds ratio of 0.28 and 0.08 in all breeds, and in Anglo-Nubian, respectively, with significant association (P0.05) that inferred 0.28 and 0.08 times greater probability in all breeds, and in Anglo-Nubian, respectively, for subclinical mastitis to occur than those of other genotypes. Genotype AB showed odds ratio of 3.83, 13.00 and 2.40 in all breeds, in Anglo-Nubian, and in Upgraded, respectively, with significant association (P0.05) that indicated 3.83, 13.00 and 2.40 times more likely in all breeds, in Anglo-Nubian, and in Upgraded, respectively, to suffer subclinical mastitis than those of other genotypes. In Study 3, genetic expression analysis showed a significant upregulation of TLR4 gene up to maximum of 3.63-fold in goats without subclinical mastitis compared to subclinically mastitic animals with only 0.65-fold which suggest a prompt role of TLR4 gene in the protection of animal against possible infection.